Efektivitas layanan bimbingan kelompok untuk mengurangi perilaku bullying pada siswa di SMP Negeri 126 Jakarta Timur - Dianita Wulansari; Devi Ratnasari; Rezky Permatasari (TERAPUTIK: Jurnal Bimbingan dan Konseling, 2019)
The purpose of this research is knowing the effectiveness of group guidance service to decreasing bullying behavior at SMP Negeri 126 Jakarta Timur. This research used quantitative method with one group pre-test and post-test design. The sample that used for this research is 10 students who have severe bullying behavior and use purposive sampling to determine the data. Researcher used Wilcoxon sign rank to analyze the data. The conclusion of this research, is group guidance service ineffective to decreasing bullying behaviour at SMP Negeri 126 Jakarta Timur